MathAR Book Technology Innovation: Effectiveness of Using Augmented Reality-Based Mathematics Books on Students' Mathematical Understanding Ability - Prihatini, Atik; Dewi, Utami; Pramuditya, Surya Amami; Aminah, Neneng (PT Inovasi Pratama Internasional, 2024)
Educational innovation continues to develop with advances in digital technology, including the use of Augmented Reality (AR) in learning. This research aims to measure the effectiveness of AR-based mathematics books (MathAR Book) on students' mathematical understanding. MathAR Book integrates traditional learning content with AR elements such as 3D visualization and interactive animations to increase student interest and engagement in learning mathematics. This research methodology uses a quasi-experimental approach with a pretest-posttest design. The sample consisted of class XII students who were randomly selected and divided into an experimental group that used the MathAR Book and a control group that used conventional textbooks. The instruments used include tests of understanding mathematical concepts, learning motivation questionnaires, and in-depth interviews. The results showed a significant increase in students' mathematical understanding in the experimental group compared to the control group. MathAR Book students also showed increased learning motivation and concept visualization abilities. Student feedback indicates that AR creates a more engaging and effective learning environment. In conclusion, the MathAR Book effectively improves students' mathematical understanding.